Cell wall polysaccharides and mono-/disaccharides as chemical determinants for the texture and hygroscopicity of freeze-dried fruit and vegetable cubes. (30th November 2022) - Feng, Shuhan; Bi, Jinfeng; Yi, Jianyong; Li, Xuan; Li, Jiangkuo; Ma, Youchuan
Highlights: Cell wall polysaccharides constructed the scaffold of freeze-dried cubes and inhibited structural collapse. Natural starch granules blocked collapse as fillers and reduced crispiness. Mono-/disaccharides were responsible for the hardness and crispiness. Mono-/disaccharides reduced the size of porous structures and rendered severe shrinkage. Polysaccharides decreased the hygroscopicity, but mono-/disaccharides, especially fructose, promoting hygroscopicity. Abstract: In order to select the critical factors on the texture and hygroscopic characteristics of freeze-dried fruit and vegetable cubes, the correlation analysis was performed on the major chemical compositions of 12 fresh materials, and the microstructure, texture, hygroscopicity of corresponding freeze-dried samples. The dry proportion of starch-rich materials, such as taro, was mainly composed of polysaccharides (0.76–0.89 g/g db), while the dry proportion of starch-poor materials such as apple was mainly composed of mono-/disaccharides (0.70–0.95/g db). Data from the microscopy showed that cell wall polysaccharides constituted the scaffold of freeze-dried cubes and natural starch granules attached to the scaffold as fillers. Both of them inhibited structural collapse. Mono-/disaccharides were accountable for the hardness and crispiness of freeze-dried cubes, however, excessive mono-/disaccharides could reduce the size of the pores and cause severe shrinkage. Polysaccharides reduced the hygroscopicity of freeze-dried cubes, on the contrary, mono-/disaccharides promoted hygroscopicity, especially fructose.